Application Of Vehicle Routing Problem Using Clarke And Wright Algorithm For Distribution Of White Sugar By â€œToko Bersama Traderâ€ - Morihito, Rondo; Montolalu, Chriestie; Pinontoan, Benny (d'CARTESIAN:Jurnal Matematika dan Aplikasi, 2018)
The problem which is often experienced in the delivery of goods from distributor to the destination is the delivery route which is not sufficient with the capacity of the vehicle. This matter is very important because it can affect the trust of the clients on the shippers in the distributor. This problem can be analyzed using Capacitated Vehicle Routing Problem (CVRP) with Clarke and Wright Algorithm. This research begins with determining the distance between all coordinates with Euclidean Distance, making the distance matrix between places to go. After that, the calculation CVRP using Clarke and Wright Algorithm is exected in this study, a calculate CVRP using Clarke and Wright algorithm can help of the computer. The study was conducted at 15 shop coordinates, the results obtained by 4 routes with total load 3750 kg and distance 29.8510 km. Route of delivery the first route 1100 kg load and distance 11.5963 km, second route 1000 kg load and distance 6.6493 km, third route 1000 kg load and distance 2.7549 km, and the fourth route 650 kg load and distance 8.8505 km.Keywords: Distributor, Vehicle Routing Problem, Capacitated Vehicle Routing Problem, Clarke and Wright Algorithm